If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45 + (9x + -1) = 90 Reorder the terms: 45 + (-1 + 9x) = 90 Remove parenthesis around (-1 + 9x) 45 + -1 + 9x = 90 Combine like terms: 45 + -1 = 44 44 + 9x = 90 Solving 44 + 9x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-44' to each side of the equation. 44 + -44 + 9x = 90 + -44 Combine like terms: 44 + -44 = 0 0 + 9x = 90 + -44 9x = 90 + -44 Combine like terms: 90 + -44 = 46 9x = 46 Divide each side by '9'. x = 5.111111111 Simplifying x = 5.111111111
| r/31=22 | | 3*-3m-1-3m+6=2-9 | | y^2-6y-1=0 | | 4m-6=4 | | 12u=144 | | 2(5a-11)+3=11 | | 406=f-61 | | (2+3i)(8-5i)=0 | | 57+11x=90 | | 20k=280 | | X^2/.15 | | 17.1/1.1 | | d-257=86 | | (5a-4)(3a+2)=0 | | 48=x+y | | 2(8x+64x)=10x+268 | | p-327=415 | | r-191=70 | | 6y=7-4x | | 9r+2=19r+4 | | r-67=164 | | 2-z/2.05=-15 | | 1.5f-5=1 | | m-157=597 | | -3.75y=8 | | 11y=550 | | 2/7(4m-18=12 | | 60+c+90=180 | | 17v=102 | | 8y-7-4y=74-5y | | 7(2x-11)=3(2x-4)+7 | | 13v=559 |